The Benefits of Ice Baths on Delayed Onset Muscle Soreness after high intensity training - Marta Rutkowska; Mateusz Bieńko; Tomasz Król; Michalina Toborek; Magdalena Marchaj; Karolina Korta; Anna Putra; Natalia Niedziela; Mikołaj Margas (Kazimierz Wielki University, 2024)
Introduction: In the field of sports and exercise science researchers are exploring methods to enhance recovery after training sessions. One popular approach that has gained attention is the use of ice baths. Purpose: This review examines how ice baths impact muscle recovery time following high intensity workouts looking at both the effects and practical considerations with a focus, on Delayed Onset Muscle Soreness (DOMS). The PubMed database was used in this study. A literature review was conducted using the keywords: "cold water", "muscle regeneration", "muscle soreness", "DOMS" and "ice bathing". State of Knowledge: Ice baths have been found to trigger vasoconstriction reduce inflammation and alleviate muscle soreness. However, their effectiveness in reducing exercise-induced inflammation and muscle soreness remains uncertain. The impact on DOMS varies among individuals due to factors like genetics, age, gender and health conditions. This variability highlights the challenges of incorporating ice baths into workout recovery routines. Summary: The use of ice baths in post-exercise recovery presents a complex landscape with diverse physiological responses and variable outcomes. While practical guidelines exist for the application of ice baths in high-intensity training, debates persist regarding their efficacy on DOMS compared to active recovery. While ice baths are incorporated into holistic recovery strategies conflicting research casts doubt on their standalone effectiveness prompting further exploration of how they complement other recovery methods. Moreover, potential drawbacks and conflicting evidence regarding their influence on long-term training adaptations raise questions about the overall costs and benefits.